Engel's Law, Diet Diversity, and the Quality of Food Consumption. (23rd September 2017) - Clements, Kenneth W.; Si, Jiawei
Abstract : Increasing income brings about a decline in the relative importance of food consumption, a wider spread of spending patterns, and a demand for higher‐quality goods. Using an index‐number approach, this article analyzes these three closely‐related tendencies. Stripping out the impact of prices from the dispersion of food expenditures gives a volume‐based measure of diet diversity that is relevant for nutrition. Using unpublished data from the World Bank's International Comparison Program for 31 items of food in more than 150 countries, we find that diets of rich countries are substantially more diverse than those of the poor; and that volumes are the more appropriate way to measure the inequality of diversity. The quality of the food basket, based on the luxury‐necessity distinction of consumption, increases with income, but the elasticity is small. There is a modest tendency for the structure of prices to be regressive since prices of luxuries relative to necessities are lower in richer countries. Additionally, our diversity and quality measures are shown to have implications for demand analysis and well‐being.